Pengukuran Total Petroleum Hidrokarbon (TPH) Melalui Pendekatan Kadar Minyak-Lemak dalam Sedimen di Perairan Delta Cimanuk, Jawa Barat - Wulandari, Ita; Yogaswara, Deny; Khozanah, Khozanah; Edward, Edward; Rositasari, Ricky; Falahudin, Dede (OLDI (Oseanologi dan Limnologi di Indonesia), 2019)
Determination of Total Petroleum Hidrokarbon (TPH) through the Concentration of Oil and Grease (OG) in the Surface Sediment of Cimanuk Delta Waters, West Java. The Estuary of Delta Cimanuk is located in the coastal water of Indramayu, West Java. The pollution in the Cimanuk Delta was originated from households and industrial waste on coastal dan upland areas. Coupled with the traffic activities of fishing vessels at the fish landing (PPI) and fishing port (PP) bases around the waters, oil and grease contamination would be a threat as pollution in Indramayu coastal area. The major source of OG component on coastal waters was animal and vegetal fat and total petroleum hydrocarbon (TPH). The objectives of the study are to estimate the concentration and spatial distribution of TPH in the sediments of the Cimanuk watershed based on OG levels, and identifying the distribution of TPH-contaminated areas. Fourier Transform Infrared Spectroscopy (FTIR) instrument was applied to determine OG compounds in the sediment samples.  The results showed that OG concentrations in sediments were varied between <1 to 138.104 mg kg-1 dry weight (dw), while TPH was estimated at 0.24 ? 36.60 mg kg-1 dw. The highest concentrations of OG was observed on St-10 in the northeast coast. Compared to the threshold value of sediments quality guidelines according to ANZECC (OG: 280-550 mg kg-1 dw), the TPH levels in eighteen observation stations were within normal range. The increased pollutant intake in Cimanuk watershed will threat the estuary as well as its biodiversity.